2005
DOI: 10.1111/j.1467-940x.2005.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Broadband and Economic Development: A Municipal Case Study From Florida

Abstract: In this paper, we explore whether broadband investment by municipalities has an effect on economic growth. To do so, we employ an econometric model to compare economic growth between counties in the State of Florida. Our econometric model shows that Lake County – a small county in central Florida – has experienced significantly greater growth in economic activity relative to comparable Florida counties since making its municipal fiber‐optic network generally available to businesses and municipal institutions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 24 publications
4
35
0
2
Order By: Relevance
“…Similarly, investment in ICTs and telecommunication or broadband infrastructure were shown to be positively related to growth in OECD countries (Koutroumpis, 2009;Röller & Waverman, 2001). Municipal level studies in the United States and national-level studies in other Western countries and China find similar results (Ford & Koutsky, 2005;Kumar et al, 2016;Oulton, 2002).…”
supporting
confidence: 68%
“…Similarly, investment in ICTs and telecommunication or broadband infrastructure were shown to be positively related to growth in OECD countries (Koutroumpis, 2009;Röller & Waverman, 2001). Municipal level studies in the United States and national-level studies in other Western countries and China find similar results (Ford & Koutsky, 2005;Kumar et al, 2016;Oulton, 2002).…”
supporting
confidence: 68%
“…Urban planning and government policies also play an important role in the making of a wireless city [34]. For example, through a comparative study of Singapore and Taipei, Hu et al [5] suggested that the development of the wireless city in Taipei is mainly driven by top-down government policy while such development depends more on the market-driven participation of customers in Singapore.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Selain sektor swasta, sektor publik juga mengalami pertumbuhan ekonomi yang signifikan sebagaimana yang terjadi di Lake County, Florida, Amerika Serikat (G.S. Ford, T. M. Koutsky, 2005). Studi lainnya menunjukkan bahwa pemanfaatan teknologi pitalebar pada sektor industri memberikan dampak terhadap industri termasuk pertumbuhan lapangan pekerjaan meskipun memang tidak semua jenis industri mengalami pertumbuhan lapangan kerja sebagaimana yang terjadi di Kentucky, Amerika Serikat (Shideler D., Badasyan N., 2007).…”
Section: Tinjauan Pustakaunclassified